2013
DOI: 10.1124/dmd.112.050211
|View full text |Cite
|
Sign up to set email alerts
|

RNA-Sequencing Quantification of Hepatic Ontogeny and Tissue Distribution of mRNAs of Phase II Enzymes in Mice

Abstract: Phase II conjugating enzymes play key roles in the metabolism of xenobiotics. In the present study, RNA sequencing was used to elucidate hepatic ontogeny and tissue distribution of mRNA expression of all major known Phase II enzymes, including enzymes involved in glucuronidation, sulfation, glutathione conjugation, acetylation, methylation, and amino acid conjugation, as well as enzymes for the synthesis of Phase II cosubstrates, in male C57BL/6J mice. Livers from male C57BL/6J mice were collected at 12 ages f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
57
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(65 citation statements)
references
References 53 publications
8
57
0
Order By: Relevance
“…The present findings of XPG expression in the liver are consistent with previous RNA-Seq reports in adult male mice (Cui et al, 2012;Peng et al, 2012Peng et al, , 2013Lu et al, 2013). The present study is novel because it has unveiled the true quantification of XPGs in various sections of the intestine, in comparison with that in liver.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The present findings of XPG expression in the liver are consistent with previous RNA-Seq reports in adult male mice (Cui et al, 2012;Peng et al, 2012Peng et al, , 2013Lu et al, 2013). The present study is novel because it has unveiled the true quantification of XPGs in various sections of the intestine, in comparison with that in liver.…”
Section: Discussionsupporting
confidence: 92%
“…The result of RNA-Seq is expressed as fragments per kilobase of exon per million reads mapped (FPKM), which normalizes the sequencing depths between different samples and sizes between various genes, allowing a direct comparison of various transcripts on a genome-wide scale (Malone and Oliver, 2011). We have previously conducted RNA-Seq experiments on the ontogeny of various XPGs in mouse livers (Cui et al, 2012;Peng et al, 2012Peng et al, , 2013Lu et al, 2013;Selwyn et al, 2015), but a systematic characterization of the XPGs in various sections of the intestine in comparison with liver tissue is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…We and other investigators have shown that the expression of biotransformation genes is developmentally regulated in rodents and humans (Morgan et al, 1994; Yang et al, 2009; Hines, 2013; Lu, 2013; Peng et al, 2013). Based on immunoblotting analysis (Morgan et al, 1994), one to two week old rats express no hydrolase A or B, two major rat carboxylesterases.…”
Section: Introductionmentioning
confidence: 88%
“…More importantly, RNA-Seq quantifies the true abundance of mRNA molecules in biologic samples and enables comparison of the expression of all genes (Malone and Oliver, 2011). We have reported that RNA-Seq can reveal ontogenic patterns of P450s (Peng et al, 2012), phase-II enzymes (Lu et al, 2013), transporters (Cui et al, 2012a), and epigenetic modifiers in the mouse liver during maturation.…”
Section: Introductionmentioning
confidence: 99%